Effect of perforations and slits on hygrothermal properties of EPS - Mergim Gaši; Bojan Milovanović; Ivana Banjad Pečur; Marina Bagarić (Građevinar)
This paper presents the results of research on the influence of perforation and slits on the water vapour diffusion of expanded polystyrene (EPS) and the influence of the size and number of perforations and slits on the thermal conductivity of EPS board. The research was conducted using numerical models (control volume methods) with varying sample thickness, slit spacing, and depth and diameter of perforations. The numerical model showed that it is possible to obtain up to 42.18 % better water vapour diffusion compared to EPS board without perforation with an increase in thermal conductivity of 9.02 %. Also, the results of this study show that the effective vapour diffusion coefficient depends on the thickness of the perforated EPS samples.